The Intergenerational Transmission of Discrimination: Children's Experiences of Unfair Treatment and Their Mothers' Health at Midlife. (December 2019) - Colen, Cynthia G.; Li, Qi; Reczek, Corinne; Williams, David R.
A growing body of research suggests that maternal exposure to discrimination helps to explain racial disparities in children's health. However, no study has considered if the intergenerational health effects of unfair treatment operate in the opposite direction—from child to mother. To this end, we use data from mother–child pairs in the National Longitudinal Survey of Youth 1979 to determine whether adolescent and young adult children's experiences of discrimination influence their mother's health across midlife. We find that children who report more frequent instances of discrimination have mothers whose self-rated health declines more rapidly between ages 40 and 50 years. Furthermore, racial disparities in exposure to discrimination among children explains almost 10% of the black–white gap but little of the Hispanic–white gap in self-rated health among these mothers. We conclude that the negative health impacts of discrimination are likely to operate in a bidirectional fashion across key family relationships.